Performance evaluation of optical attocells configuration in an indoor visible light communication - M.S. M. Gismalla; M.F. L. Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Visible light communication VLC is deemed as futuristic technology applied for both illumination and data communication due to the low-cost energy consumption, long life expectancy, huge bandwidth, and high security compared to radio frequency RF. Uncovered area, minimum signal-to-noise ratio (SNR) and received power results from the non-uniform distribution of small base stations (i.e. Optical attocells) in the room. In this paper, the researchers propose a new LEDs distribution of five optical attocells configuration model in order to optimize the received power distribution and SNR at the center of the room for indoor VLC system. The optical attocells configuration in terms of received power to fill the uncovered area at the center of the room has been investigated. The simulation results showed that the proposed attocells configuration saved 24.9% of the transmitted power. Besides that, the whole room was covered uniformly.  As a result, the received power and SNR are improved.